(3TQM JYdje GdeJYde WQjb GdJYdes - (3GHf ESeGYjds; (3GdRQfhLj , HQgGf GdOjf EHQGgje Hf ESeGYjd GdRQfhLj,J (B593 (3g` s ((3ReTJhi s)
(3ChdgG (B:s
(3HSe Gddg GdQMe GdQMje GdMeO ddg GdPi CfYe YdjfG HCfhGY GdfYe adeG QCjJ GdcJGH GdeSei HJYdje GdeJYde eQZhHkG hebHhdkG Hjf Chdi GdJYdje hGdJYde hcGf ai HYV fXeg hfTQg ehGVY eMJGLI dcTa GSJGQg CQOJ Cf CTQM TQMkG jHjf ebGUOg s
(3BNQgG (B:s
(3ai GdcJGH GdeSei HWH GdfHi Ydjg GdSdGe hcCf bGFdkG bGd aCjf JLO Pdc GdcJGH Je GdcJGH HYhf Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdg hbajI HGSe YdGeI HjQhJ GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi eDQN SfI (B1373(3g`s
(3aQZ GdeDda ef JCdja GdcJGH SfI(B965(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdeYGQa GdYGeIs